(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2025)
This study investigates the factors influencing users’ satisfaction and trust in digital government services, focusing on the Technology Acceptance Model (TAM) (perceived usefulness, and ease of use) and the Unified Theory of Acceptance and Use of Technology (UTAUT) (effort expectancy, social influence, and performance expectancy). The study employs a quantitative research approach, utilizing snowball sampling to collect data from users of e-government services in Saudi Arabia. The data is analyzed using statistical techniques, including Structural Equation Modeling (SEM), to test the research hypotheses. Effort expectancy, usefulness, ease of use, and social influence drive user satisfaction, with effort expectancy being the key factor. Satisfaction boosts trust in digital platforms. Performance expectancy, however, does not appear to affect satisfaction, likely due to cultural or contextual factors specific to Saudi Arabia. Although this study is valuable, it has limitations, including potential sampling bias. Future research should consider additional contextual factors, diverse cultures, and moderators such as cultural influences and individual differences. Longitudinal and qualitative studies could enhance understanding of the user’s satisfaction and trust in digital government services in Saudi Arabia. This study integrates the Theory of Acceptance and Use of Technology (TAM) and the Unified Theory of Acceptance and Use of Technology (UTAUT) to examine factors influencing user satisfaction and trust in digital government services in Saudi Arabia. The findings that shape user satisfaction and trust contribute to the academic discourse on digital government services and provide practical implications for policymakers, IT developers, and government entities who are concerned with developing e-government services.